Baroreflex deficit are associated with target organ damage - Paulini, Janaina (O Mundo da Saúde, 2017)
RETRACTED The editorial team of the Journal O Mundo da Saúde communicates the formal retracted the article: PAULINI, Janaina. Baroreflex deficit are associated with target organ damage. Rev. O Mundo da Saúde. 2017;40, n. A: 433-46. https://doi.org/10.15343/0104-7809.201740a433446 João Batista Gomes de Lima Editorial chief